2022
DOI: 10.3389/fncir.2022.1076354
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal relationships between sleep and smell

Abstract: Despite major anatomical differences with other mammalian sensory systems, olfaction shares with those systems a modulation by sleep/wake states. Sleep modulates odor sensitivity and serves as an important regulator of both perceptual and associative odor memory. In addition, however, olfaction also has an important modulatory impact on sleep. Odors can affect the latency to sleep onset, as well as the quality and duration of sleep. Olfactory modulation of sleep may be mediated by direct synaptic interaction b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 182 publications
1
7
0
3
Order By: Relevance
“…We found that ‘Odor’ nights had lower wake index than ‘Control’ nights (‘Odor’: 1.9 (1.37), ‘Control’: 2.2 (0.7), Wilcoxon signed-rank test (12/17 patients): z = -2.0956, p = 0.0361, BF10 = 1.958, Fig 2d), and arousal scores (both cortical and autonomic), were not significantly different between the two nights (Arousal total sleep: ‘Odor’: 32.9 (26.12), ‘Control’: 26.9 (16.05), Wilcoxon signed-rank test (12/17 patients): z = -1.585, p = 0.113, BF10 = 0.855). These findings indicate that odor stimulation did not induce arousals and, in line with the literature 25 reduced the number of awakenings.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…We found that ‘Odor’ nights had lower wake index than ‘Control’ nights (‘Odor’: 1.9 (1.37), ‘Control’: 2.2 (0.7), Wilcoxon signed-rank test (12/17 patients): z = -2.0956, p = 0.0361, BF10 = 1.958, Fig 2d), and arousal scores (both cortical and autonomic), were not significantly different between the two nights (Arousal total sleep: ‘Odor’: 32.9 (26.12), ‘Control’: 26.9 (16.05), Wilcoxon signed-rank test (12/17 patients): z = -1.585, p = 0.113, BF10 = 0.855). These findings indicate that odor stimulation did not induce arousals and, in line with the literature 25 reduced the number of awakenings.…”
Section: Resultssupporting
confidence: 90%
“…It is largely held that olfactory stimulation does not perturb sleep, and as discussed earlier, may promote it [24][25][26][27][28][29][30] . Nevertheless, in order to validate that in our experimental setting the olfactory stimulation did not arise from sleep, we compared the wake and arousal indices of 'Odor' and 'Control' nights.…”
Section: Olfactory Stimulation Did Not Promote Arousal or Alter Sleep...mentioning
confidence: 98%
See 1 more Smart Citation
“…O uso de aromaterapias está associado ao sono, já que a manutenção do sono pode ser influenciada pelo sistema sensitivo. Pode-se citar como exemplo a presença do cheiro materno, que é capaz de reduzir o choro e induzir os comportamentos para a alimentação no recém-nascido, o que acaba acelerando o processo de sono (Gaeta & Wilson, 2022). O mecanismo olfatório, que é capaz de regular o sono, está relacionado a circuitos neuronais em múltiplas interconexões, provocando assim uma modulação no processo de sono e vigília, além da uma estabilização.…”
Section: Fatores Que Influenciam O Pré-sonounclassified
“…É possível fazer uma análise de que os odores iram afetar e ativar o circuito noradrenérgico locus coeruleus e o núcleo dorsal da rafe serotoninérgica, que são componentes que podem induzir a liberação alta de cortisol durante as atividades. O uso de aromaterapia é dependente de uma especificidade, sendo uma associação entre o efeito que o odor é capaz de produzir na pessoa, parte biomolecular, e nas preferências e memórias associadas (Gaeta & Wilson, 2022).…”
Section: Fatores Que Influenciam O Pré-sonounclassified